The inverse of function f(x) = x/4 - 2 is:
f^(-1)(x) = 4(x + 2).
Option C is the correct answer.
We have,
To find the inverse of the function f(x) = x/4 - 2, we can follow these steps:
Step 1: Replace f(x) with y: y = x/4 - 2.
Step 2: Swap the variables x and y: x = y/4 - 2.
Step 3: Solve the equation for y.
Let's start by isolating y:
x = y/4 - 2
x + 2 = y/4 (Adding 2 to both sides)
4(x + 2) = y (Multiplying both sides by 4)
So, the inversefunction is y = 4(x + 2).
However, it's common to write the inversefunction with the variable x instead of y.
Therefore,
The inverse of function f(x) = x/4 - 2 is:
f^(-1)(x) = 4(x + 2).
Learn more about functions here:
#SPJ2
Answer: (x, y)
Step-by-step explanation:
Answer:
(x,y)
Step-by-step explanation:
Answer:
Step-by-step explanation:
(-3,12) and (-8,17)
y2 = 17, y1 = 12 , x2 = -8, x1 = -3
Slope m = (y2 - y1)/(x2 - x1)
m = (17 - 12)/(-8 + 3)
m = 5/-5
m = -1
Answer:
- 5/11
Step-by-step explanation: